Loss of smell/taste is a potential indicator of a mild case of COVID-19: a retrospective institutional study - Gautam, Harendra Kumar; Tripathi, Shalani; Srivastava, Amrita; Verma, Ruchika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: COVID-19, the respiratory disease caused by the new coronavirus. The loss of smell is an atypical symptom and is usually associated with milder form of this disease compared to severe disease. The aim of this study was to compare the severity of disease in patients with and without loss of smell/taste. Methods: This was a retrospective study of 100 patients who were COVID RT-PCR positive, carried out in the COVID care center of a tertiary hospital during the period of 6 months from October 2020 to April 2021. Results: 100 cases of RT-PCR positive patients were divided into two groups (50 cases each of patients with and without loss of smell/taste). The mean age was 55-65 years in both the groups. Throat pain/throat irritation and fever were the most common complaints in the patients of both groups, affecting all the 100 (100%) patients. It was followed by cough in 25 (50%) patients and diarrhea in 12 (24%) patients. 2 (4%) patients had breathlessness in group A. While in group B, 50 (100%) patients had cough and breathlessness. The average SpO2 was >95 in 45 (90%) patients in group A while in group B, <90 in 30 (60%) patient and >95 in 8 (16%) patients. The CT values of HRCT thorax were <8 in 45 (90%) patients in group A while in group B, >15 in 25 (50%) patients. Conclusions: The treatment outcome was 100% patients being discharged in group A without any complication while in group B, 38 (76%) patients were discharged and 12 (24%) patients expired due to various COVID-19 related complications. From this we conclude that, loss of taste and loss of smell are prognostic indicators of mild type of COVID-19.